(untitled) (FULafia Journal of Science and Technology, 2020)
Geochemical characterization of three clay occurrences in Igbanke, Esan and Asaboro area of Edo State were investigated for main oxides, minor and rare earth elements to unravel paleodepositional, source area past weathering condition. Inductively coupled plasma-optical emission spectrometry (ICP-OES) and inductively coupled plasma-mass spectrometry techniques were deployed to analyse the samples. Al2O3 and Fe2O3 depletion (13.63 - 30.46 wt. % and 0.38 – 5.09 wt. %) relative to SiO2 (36.64 - 72.84 wt. %), close to the Post Achaean Australia shales and Upper Continental Crust standards of 62.8% and 66% respectively were recorded. Except Y, Zr, Hf, Ga, concentration of trace elements, are augmented relative to PAAS, although some samples show concentration ranges lower than or higher than average PAAS values. Redox-sensitive trace element proportions indicated variable paleo-redox conditions (oxic – suboxic), supported by negative cerium anomaly of -0.9 – -1.115. Low values of K2O/Al2O3 (0.03 – 0.01) suggest a probable sedimentary reprocessing or intensification in the extent of source area weathering, affirmed by increase in Al2O3 and Fe2O3 values, a sign of weathering and geochemical modification.